Climate change and fenology of birds sprig arrival - Ivanauskas, Feliksas; Lapinskas, Remigijus; Žalakevičius, Mečislovas (Lietuvos matematikos rinkinys, 2008)
The paper investigates the climate change impact on bird first spring arrival dates, including interpretation of mechanisms of changes in dates. Regression models for 46 species of birds based on data collected in Lithuania in 1966–2000are created and discussed.An explanation of changes in arrival timing is proposed.